1976
DOI: 10.1152/ajplegacy.1976.230.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of contractions and transit in rat small intestine

Abstract: A single strain gauge was implanted chronically in the proximal jejunum of the rat to record contractions. FAsted pentobarbital-anesthetized animals received glucagon, caerulein, or isotonic saline control infusions intravenously while contractions were recorded. In control animals, the distribution of contractions in time showed clusters, with peaks at intervals of 14.24 +/-5.6 (SD) min. Glucagon produced dose-related inhibition of contractions. Caerulein at two lower doses produced a more uniform distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…The mean duration of the MMC for Sprague-Dawley rats was 14.2 B 2.3 min in a previous study [13], a duration very similar to that observed by us. Compared to the telemetric method in pigs [6], no abdominal fistulas were needed and electromyographic signals could be detected from any part of the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 88%
“…The mean duration of the MMC for Sprague-Dawley rats was 14.2 B 2.3 min in a previous study [13], a duration very similar to that observed by us. Compared to the telemetric method in pigs [6], no abdominal fistulas were needed and electromyographic signals could be detected from any part of the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 88%
“…The MMC after 90% PHx was characterized by an increased duration of Phase 2-like activity. Both quantitative and qualitative changes in contractions clearly induced changes in gastrointestinal transit [14]. These findings suggest FIG.…”
Section: Discussionmentioning
confidence: 68%
“…It is interesting to note that the MI at 1 day after surgery was higher than those at 3 days after surgery in 90% PHx ϩ bile groups. Although the mechanism remains unclear, this result may be associated with decreased intestinal sensitivity to bile because of higher levels of glucagon, which is related to inhibited gastrointestinal motility [14] in blood at 3 days after 90% PHx than at 1 day after 90% PHx [19].…”
Section: Figmentioning
confidence: 99%
“…It is thought to function as an 'interdigestive housekeeper' that sweeps the small bowel from debris etc. (17)(18)(19)(20). Ruckebusch and Fioramonti (21) found that in the duodenum of the rat, these cycles recur at the rate of about one per 20 min, and that the MMCs have a role in the propulsion of the test meal.…”
Section: Discussionmentioning
confidence: 99%